Determination and Environmental Implications of Aqueous-Phase Rate Constants in Radical Reactions. (15th February 2021) - Ma, Junye; Minakata, Daisuke; O'Shea, Kevin; Bai, Lu; Dionysiou, Dionysios D.; Spinney, Richard; Xiao, Ruiyang; Wei, Zongsu
Highlights: MS excel spreadsheets were built to demonstrate the k determination processes. We evaluated different k measurement methods for the radical-induced reactions. We provided critical evaluations on their advantages and disadvantages. We proposed a standard operation procedure for the k determination. This is the first review covering methodological approaches and considerations. Abstract: Interests in the kinetics of radical–induced reactions in aqueous solution have grown remarkably due to their water engineering significance ( e.g ., advanced oxidation processes). Although compilations of the rate constants ( k ) for various radicals have been documented, surprisingly a systematic review has yet to be reported on the development of reliable methods for determining k values. A knowledge gap exists to critically evaluate and screen the various methods to measure them. In this review, we summarize the direct and indirect methods under steady–state and non–steady–state conditions, followed by critical evaluations on their advantages and disadvantages. The radicals of ·OH, SO 4 · −, O 2 · −, and Cl· were chosen based on their significant aquatic environmental relevance. MS excel spreadsheets that demonstrate the determination processes were provided allowing one to reproduce the data and/or to analyze the unprocessed raw data as a "template". We formulated a standard operation procedure for the k determination, although there is simply no "versatile" method fitting for all radical reactions. Finally, existing challenges and future research focus are discussed. This is the first review covering methodological approaches and considerations, aiming to provide a holistic and fundamental basis to choose an appropriate method for determining the k values for bimolecular reactions between target compounds and radicals in the aqueous phase. Graphical abstract: Image, graphical abstract